DEVELOPING A PLASTIC WASTE MANAGEMENT PROGRAM: FROM RIVER BASINS TO URBAN BEACHES (CASE STUDY) - Moura, Micaella R.F.; Falcão, Symone M.P.; da Silva, Alisson Caetano; Neto, Alfredo Ribeiro; Montenegro, Suzana M.G.L.; da Silva, Simone Rosa (Journal of Engineering and Technological Sciences, 2020)
Solid waste accumulation in coastal environments has been a growing concern. In the coastal megacity of Recife, Pernambuco state, Brazil, plastic waste issues currently exist both at the ocean scale and river basin scale. The city is known as the ?Brazilian Venice? thanks to the Capibaribe River, which crosses many neighborhoods, running in a west-east direction into the Atlantic Ocean. This paper provides the initial basis to develop a Plastic Waste Management Program proposal for implementation in the city of Recife, given the lack of resolutions that have looked at plastic waste management through integrated water environment scales (from river basin to ocean). The methodology used included articulation and documental collection from four main public agencies from the state/city and stakeholders. The results showed its relevance for better plastic waste management in Recife, considering an integrated water environment on a river basin-to-ocean scale by using the recognized major connected water environments (Capibaribe river and Boa Viagem beach). Similar integrated program proposals could be made for other coastal areas, enabling not only the identification of fragilities but also the exchange of information regarding the theme.